THE EFFECT OF USING VIDEO ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Eka Desi Ariyuni and Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
The objective of this study was to investigate whether video significantly affected on students’ achievement in writing procedure text. This study was an experimental research design. The population of this study was grade XI students of SMA Swasta Sinar Harapan Lubuk Pakam with 70 students as samples who were divided into two groups, namely experimental and control group. The experimental group was taught by using video, while the control group was taught by without video. The instrument of collecting data was essay tests. The data were analyzed by using t-test formula. The result of the analysis showed that tvalue is higher than ttable (4.79 > 2.00) at the level of significance 0.05 with the degree of freedom (df) 68. It implies that video is appropriate to be applied for writing procedure text.